PHYSIOLOGICAL ANALYSIS AND BACTERIOLOGICAL QUALITY OF OGUN RIVER, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Pollution pressures in form of untreated wastes are exerted on Ogun River via human activities. This river serves as a main source of drinking water to animals waiting to be slaughtered for human consumption and for other domestic purposes by local resident. This research was carried out to determine effects of abattoir effluents on physicochemical parameters and microbial quality of Ogun River. Water and soil samples from the abattoir were subjected to physicochemical analysis by standard methods. Bacterial population were isolated from both samples by standard cultural methods and identified by standard biochemical characterization. Physicochemical analysis showed the pH, temperature, and nitrate are appreciably within normal recommended limits while other parameters exceeded recommended limit for public safety. The total viable count for all the samples which was between 1x104 and 9.2x102 cfu/ml. This exceeded the WHO permissible limit of 1x102 cfu/ml. The bacterial isolates that were identified includes; Bacillus subtilis, Escherichia coli, Salmonella spp, Staphylococcus spp Acinetobacter spp, Comomonas sp., Pseudomonas stutzeri, and Aeromonas hydrophila. The findings of this work underscored the need for proper and efficient effluents treatment system suitable for the reduction of toxic constituents and pathogens that are capable of causing public health hazard.
Keywords: Pollution, Physico-chemical parameters, Effluents